Multi-Objective and Goal-Programming Approaches as a Distance Function Model - Romero, Carlos (The Journal of the Operational Research Society, 1985)
This note shows that virtually all the multi-objective and goal-programming approaches can be thought of as special cases of a general distance-function model. Although the outcome of this paper cannot be considered completely new, it can, however, help increasing conceptual clarity and precision in future dialogue, showing the actual links between multi-objective programming, goal programming and traditional mathematical programming.